Identification of Mercury Content in Children Stunting Patients Aged 0–24 Months in the Regions Small Scale Gold Mine in Krueng Sabee District, Aceh Jaya Regency - Lensoni; Nurdin, Ambia; Ismaturrahmi (Postgraduate, University of Mataram, 2023)
Mercury is a type of heavy metal that is included in the category of Hazardous and Toxic Materials (B3) waste because it can harm living things and pollute the environment. Community mining activities are generally known to be the largest contributor of mercury to the environment. In addition, people's mining activities can indirectly result in the destruction of the landscape and vegetation on it. Mercury exposure can have a negative impact on the health of children living in ASGM areas. A reduced immune response or immune system in children living in ASGM areas with a high risk of exposure to mercury and exacerbated by concomitant malnutrition is very at risk of stunting. this study aims to identify mercury content in children stunting patients aged 0–24 months in the region's small-scale gold mine in Krueng Sabee district, Aceh Jaya Regency. The AAS instrument is used to analyze urine mercury levels. Three of the 11 urine samples did not show mercury, while the remaining 08 samples were found to contain mercury, each of the 08 urine samples was found to have mercury levels exceeding the acceptable threshold (7μg/L) Human Biomonitoring (HBM), while three twenty-nine samples had urine mercury levels below the threshold. This study concluded that 88% of stunted toddlers were found to contain mercury that exceeded the threshold. Meanwhile, 03 urine samples did not contain mercury.